Indebtedness and mental health in China: the moderating roles of income and social support - Liu, Jiankun; Zhang, Yueyun (Frontiers in Public Health, 2024)
Objective: To explore the effect of indebtedness on mental health and the moderating effects of two types of coping resources (i.e., income and social support) in the Chinese context. Methods: 41,274 adults from four waves of China Family Panel Studies conducted in 2012, 2016, 2018, and 2020. Center for Epidemiologic Studies Depression Scale was used for investigation. Pooled ordinary least squares regressions were used to examine the effect of indebtedness on mental health and the moderating effects of income and social support. Stata 16.0 was used to conduct data analysis. Results: The results showed that indebtedness had an adverse effect on mental health among Chinese adults. Furthermore, debtors with higher incomes showed fewer mental disorders than those with lower incomes. In terms of social support, monetary support from relatives was able to moderate the negative effects of indebtedness; however, the moderating effects of emotional support were negligible. Conclusion: The results of this study indicated the adverse mental health outcomes of indebtedness in emerging economies and highlighted that economic resources played protective roles against debtors’ mental disorders.